AI and Cultural Sensitivity: Student Perceptions of How AI Handles Religion, Identity, and Tradition in Texts - Khuloud Alouzi; Abdulrauf Atia; Sara Omran; Safa Alrumayh; Hajer Albshkar; Entisar Alatrish; Mowafg Masuwd; Bushra Alfallah (Muaddib: Journal of Islamic Teaching and Learning, 2026)
AI tools are increasingly used by university students to comprehend literary and cultural texts, but in Libya this use becomes sensitive when texts include religion, identity, and tradition, where misrepresentation may affect respect and classroom trust. This study aims to examine students’ perceptions of AI cultural sensitivity and the risks of bias in literature and culture learning at the University of Zawia. The study used a mixed-methods design, combining a questionnaire survey of 500 undergraduate students from the Faculties of Arts, Education, and Languages and Translation (124 males, 376 females) with semi-structured interviews with 10 lecturers. Survey findings show that AI use is common, with most students using AI at least weekly for text comprehension, cultural/historical context, writing support, and translation. Students reported moderate perceptions of AI cultural sensitivity, but high concern about misrepresentation, especially oversimplification of religious meanings, misunderstanding culture-specific terms, and biased framing. Students also showed a very strong preference for responsible-use governance, including verification practices, lecturer guidance, and AI literacy training. Faculty comparisons indicated higher perceived learning value among Languages and Translation students, while gender differences were minimal except for slightly stronger governance expectations among females. The study implies that AI can be integrated as a contextual support tool, but universities should provide clear guidelines and training to protect cultural respect and critical evaluation in sensitive topics.